Bionic bone / cartilage double-layer composite scaffold material as well as preparation method and application thereof

By designing bionic bone/cartilage double-layer composite scaffold material, combined with liquid crystal hydrogel and 3D printing technology, the problem that the existing technology is difficult to promote cartilage and bone regeneration at the same time is solved, and the directional differentiation of stem cells and the new bone/cartilage tissue is achieved. Growth, with excellent cellular affinity and drug sustained release properties.

CN119113207AActive Publication Date: 2024-12-13JINAN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411117013.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-13
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The prior art is difficult to promote the regeneration of cartilage and bone at the same time, and there are large differences in bone/cartilage tissue in structure, cell type, extracellular matrix and mechanical properties, making it difficult for a single technical means to meet the multi-level needs of composite scaffold materials.

Method used

Design a bionic bone/cartilage double-layer composite scaffold material, using the upper layer as a polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel carrying the drug that promotes cartilage active and the lower layer as a biologically functionalized chitin whisker composite A 3D printed polymer scaffold modified by LCD hydrogel channel is used to build micron radial liquid crystal channels in combination with melt deposition and freeze-drying technology.

Benefits of technology

Directed differentiation of stem cells and osteogenic/cartilage differentiation are achieved, which promotes the growth of new bone and cartilage tissues, has excellent cell affinity and drug sustained release performance, and is suitable for bone/cartilage tissue repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113207A_ABST
    Figure CN119113207A_ABST
Patent Text Reader

Abstract

The invention discloses a bionic bone / cartilage double-layer composite scaffold material as well as a preparation method and application thereof. The bionic bone / cartilage double-layer composite scaffold material is composed of an upper cartilage repair hydrogel layer and a lower bone repair scaffold layer. The method is mainly characterized in that a chitosan-chitin whisker liquid crystal composite hydrogel micron radial channel with the diameter changing in a gradient manner is constructed in a lower-layer bracket through radial freezing, and transportation of nutrient substances and recruitment, migration and adhesion of cells can be promoted; meanwhile, the drug-loaded liquid crystal hydrogel constructed in the longitudinal large channel of the stent and the upper cartilage repair layer can realize slow release of active drugs, so that stem cell osteogenesis / cartilage differentiation is further regulated and controlled, blood vessel generation is promoted, and the drug-loaded liquid crystal hydrogel is expected to be used as a bone / cartilage tissue repair material and other biomedical materials and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a bionic bone / cartilage double-layer composite scaffold material and a preparation method and application thereof. Background Art

[0002] Joint injuries are often caused by trauma, inflammation or inappropriate loads. They are a common clinical disease. Most joint injuries are manifested as damage to the upper cartilage and lower bone, accompanied by pain, swelling and stiffness, which seriously affect people's physical health and quality of life. The development of tissue engineering has made significant progress in the research on inducing tissue growth and functional regeneration based on bioactive materials. The related research on joint injury repair has gradually transformed from single cartilage repair to bone / cartilage integrated regeneration and repair. Implanting tissue engineering scaffold materials with similar properties to natural bone / cartilage is an effective repair strategy. However, bone / cartilage tissue is structurally composed of continuous but different cartilage layers and subchondral bone layers, which have great differences in cell phenotype, extracellular matrix (ECM) composition, microstructure and mechanical properties. Therefore, the development of tissue engineering scaffold materials that can promote cartilage and bone regeneration at the same time remains a huge challenge.

[0003] Clarifying the composition and characteristics of bone / cartilage can help researchers design reasonable bone / cartilage scaffold materials. On the one hand, the key to treating cartilage injury is to promote chondrocytes to secrete collagen and aggrecan to reshape the extracellular matrix of cartilage cells. However, cartilage tissue itself does not have a rich blood supply and cannot provide sufficient nutrients for chondrocyte proliferation; at the same time, cartilage does not have stem cells and cannot obtain enough chondrocytes through differentiation. On the other hand, bone injury research mainly focuses on the development of suitable bone tissue engineering scaffold materials to promote stem cell recruitment, adhesion, spreading, osteogenic differentiation and mineralization. The porous structure of the scaffold is considered to be an important factor affecting stem cell behavior and osteogenic differentiation, such as cell migration, mineral deposition, scaffold mechanical properties, and the transportation of nutrients and waste. In order to improve the growth of new bone tissue, a variety of methods have been proposed to regulate the structure of porous scaffolds. For example, salting out, freeze drying, and 3D printing customized pore structure design, etc., these methods are expected to achieve the preparation of bone / cartilage repair scaffold materials.

[0004] However, currently a single technical means cannot meet the multi-level requirements of bone / cartilage defects for scaffold materials. It is expected that scaffold materials with ideal bone / cartilage repair performance can be prepared through improvement or combination of multiple technical means. In addition, bone and cartilage ECM have liquid crystal state and viscoelastic microenvironment. Giving bone / cartilage scaffolds a liquid crystal state and viscoelastic microenvironment through reasonable means and strategies will achieve better bone / cartilage repair. Based on the above, it is of great significance to design a multifunctional scaffold material that meets the requirements of integrated and efficient repair of bone / cartilage damage in terms of composition, structure and biological function. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the primary purpose of the present invention is to provide a biomimetic bone / cartilage double-layer composite scaffold material. The scaffold material can promote cartilage, bone and angiogenesis; the upper layer is a cartilage repair hydrogel layer composed of polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel loaded with cartilage-promoting active drugs, which has a chiral topological structure in structure, is mechanically elastic, and can functionally promote cell proliferation and chondrogenic differentiation; the lower layer is a 3D printed polymer scaffold material modified with biofunctionalized chitin whisker composite liquid crystal hydrogel channels as a bone repair layer, which has micron radial liquid crystal channels and drug-loaded longitudinal liquid crystal macrochannels in structure, has a modulus and strength matching that of cancellous bone in mechanics, and can functionally recruit stem cells and osteogenic differentiation, promote new bone mineralization and angiogenesis.

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned bionic bone / cartilage double-layer composite scaffold material.

[0007] Another object of the present invention is to provide an application of the above-mentioned bionic bone / cartilage double-layer composite scaffold material.

[0008] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0009] A bionic bone / cartilage double-layer composite scaffold material, consisting of an upper cartilage repair hydrogel layer and a lower bone repair scaffold layer; the upper cartilage repair hydrogel layer is a polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel containing a photoinitiator and a cartilage-promoting active drug; the lower bone repair scaffold layer comprises a base scaffold and a liquid crystal channel structure, the base scaffold is a polymer scaffold with transverse macrochannels and longitudinal macrochannels modified by polydopamine; the liquid crystal channel structure is constructed using the base scaffold as a template, wherein the transverse macrochannel has a chitosan-chitin whisker liquid crystal composite hydrogel micron radial channel with a gradient diameter change, and the longitudinal macrochannel contains a polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel encapsulating an osteogenic and angiogenic active drug.

[0010] In the upper cartilage repair hydrogel layer:

[0011] The components in the polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel are as follows by mass percentage: 0.002% to 0.01% photoinitiator, 0.005% to 0.1% cartilage-promoting active drug, 4% to 10% chitin whisker liquid crystal, and 1% to 10% polyethylene glycol diacrylate; preferably as follows: 0.005% to 0.01% photoinitiator, 0.01% to 0.06% cartilage-promoting active drug, 5% to 8% chitin whisker liquid crystal, and 4% to 9% polyethylene glycol diacrylate.

[0012] The polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel also contains a solvent, which is the balance.

[0013] The solvent is preferably water; more preferably deionized water.

[0014] The photoinitiator is preferably at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate and 1-hydroxycyclohexyl phenyl ketone.

[0015] The cartilage-promoting active drug is preferably at least one of insulin-like growth factor, baicalin, bone morphogenetic protein, human parathyroid hormone-related protein and transforming growth factor.

[0016] The weight average molecular weight of the polyethylene glycol diacrylate is preferably 200 to 10,000, and more preferably 200 to 5,000.

[0017] In the lower bone repair scaffold layer:

[0018] The polymer is at least one of L-lactic acid, polycaprolactone and polyetheretherketone.

[0019] The weight average molecular weight of the L-polylactic acid is preferably 50,000 to 350,000, and more preferably 100,000 to 300,000.

[0020] The weight average molecular weight of the polycaprolactone is preferably 50,000 to 200,000, and more preferably 100,000.

[0021] The weight average molecular weight of the polyetheretherketone is 20,000 to 80,000, and more preferably 50,000 to 70,000.

[0022] The polymer scaffold is preferably obtained by 3D printing.

[0023] The step of modification with polydopamine is preferably as follows: placing the polymer scaffold in a dopamine reaction solution to react and obtain a matrix scaffold.

[0024] The concentration of the dopamine reaction solution is preferably 0.5 to 5 g / L; more preferably 1.5 to 4 g / L.

[0025] The reaction conditions are preferably 10-40° C. for 1-48 hours; more preferably 15-30° C. for 5-24 hours.

[0026] The large transverse channels are preferably 1 to 4 layers, with 3 to 9 channels in each layer; more preferably 2 to 3 layers, with 4 to 8 channels in each layer.

[0027] The outer diameter and inner diameter of the transverse macrochannel are preferably 1-4 mm and 0.2-1.2 mm, respectively; more preferably 2-3 mm and 0.4-1 mm, respectively.

[0028] The chitosan-chitin whisker liquid crystal composite hydrogel contains a crosslinking agent, chitosan and chitosan whisker liquid crystal; the components thereof are as follows by mass percentage: chitosan 0.5% to 5.0%, crosslinking agent 0.05% to 0.6% and chitosan whisker liquid crystal 5% to 12%; more preferably: chitosan 1% to 5%, crosslinking agent 0.1% to 0.5% and chitosan whisker liquid crystal 7% to 12%.

[0029] The chitosan-chitin whisker liquid crystal composite hydrogel also contains a solvent, which is the balance.

[0030] The solvent is mainly water, which contains acetic acid. The presence of acetic acid is conducive to the dissolution of chitosan.

[0031] The concentration of the acetic acid is preferably 1% to 3% (v / v).

[0032] The cross-linking agent is preferably at least one of genipin, glutaraldehyde and epichlorohydrin.

[0033] The diameter of the longitudinal macrochannel is preferably 0.05 to 5 mm, and more preferably 0.5 to 4 mm.

[0034] The size of the micron radial channel is 1-100 μm.

[0035] The polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel encapsulating osteogenic angiogenic active drugs contains osteogenic angiogenic active drugs, chitin whiskers and polyethylene glycol diacrylate; the components thereof are as follows by mass percentage: 0.001-0.05% of photoinitiator, 5%-15% of chitin whisker liquid crystal, 8%-15% of polyethylene glycol diacrylate, and 0.01%-1% of osteogenic angiogenic active drugs; preferably as follows: 0.005%-0.01% of photoinitiator, 8%-12% of chitin whisker liquid crystal, 9%-11% of polyethylene glycol diacrylate, and 0.05%-0.3% of osteogenic angiogenic active drugs.

[0036] The polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel encapsulating the osteogenic and angiogenic active drug also contains a solvent, which is the balance.

[0037] The solvent is preferably water; more preferably deionized water.

[0038] The weight average molecular weight of the polyethylene glycol diacrylate is preferably 200 to 10,000, and more preferably 200 to 5,000.

[0039] The osteogenic and angiogenic active drug is preferably at least one of bone morphogenetic protein, hypoxia inducible factor, vascular endothelial growth factor, transforming growth factor and deferoxamine.

[0040] The photoinitiator is preferably at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate and 1-hydroxycyclohexyl phenyl ketone.

[0041] The preparation method of the above-mentioned bionic bone / cartilage double-layer composite scaffold material comprises the following steps:

[0042] (1) constructing a polymer scaffold using fused deposition 3D printing technology, immersing the polymer scaffold in a dopamine reaction solution for reaction, and obtaining a matrix scaffold after vacuum drying;

[0043] (2) preparing a composite liquid crystal precursor solution of chitosan, a crosslinking agent and chitosan whiskers, and injecting the precursor solution into the transverse large channel of the base support obtained in step (1) for pre-crosslinking;

[0044] (3) inserting a copper rod connected to a liquid nitrogen pool into the longitudinal large channel of the matrix support, radially freezing and freeze-drying, to obtain a support with micron radial channels;

[0045] (4) preparing a precursor solution of osteogenic and angiogenic active drugs, polyethylene glycol diacrylate, a photoinitiator and chitin whisker liquid crystals, and injecting the precursor solution into the longitudinal macrochannel for photo-crosslinking to obtain a lower bone repair scaffold material;

[0046] (5) A cylindrical silicone mold is placed on the upper end of the lower bone repair scaffold material, and a precursor solution prepared by cartilage-promoting active drugs, polyethylene glycol diacrylate, photoinitiator and chitin whisker liquid crystal is dripped into the mold for photocrosslinking. The mold is removed to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0047] The polymer described in step (1) is preferably poly(L-lactic acid), polycaprolactone or polyetheretherketone wire.

[0048] When the polymer is L-polylactic acid, the 3D printing conditions are preferably: the nozzle extrusion temperature is 150-250°C, and the printing rate is 25-60 mm / min; more preferably, the nozzle extrusion temperature is 180-220°C, and the printing rate is 35-50 mm / min.

[0049] When the polymer is polycaprolactone, the 3D printing conditions are preferably: the nozzle extrusion temperature is 60-80°C, and the printing rate is 20-40 mm / min; more preferably: the nozzle extrusion temperature is 60-80°C, and the printing rate is 20-40 mm / min.

[0050] When the polymer is polyetheretherketone, the 3D printing conditions are preferably: the nozzle extrusion temperature is 340-380°C, and the printing rate is 30-50 mm / min; more preferably: the nozzle extrusion temperature is 350-360°C, and the printing rate is 40-45 mm / min.

[0051] The concentration of the dopamine reaction solution is preferably 0.5 to 5 g / L; more preferably 1.5 to 4 g / L.

[0052] The reaction conditions are preferably 10-40° C. for 1-48 hours; more preferably 15-30° C. for 5-24 hours.

[0053] The precursor solution in step (2) comprises, by mass percentage, 0.5% to 5.0% chitosan, 0.05% to 0.6% cross-linking agent and 5% to 12% chitosan whisker liquid crystal; more preferably, 1% to 5% chitosan, 0.1% to 0.5% cross-linking agent and 7% to 12% chitosan whisker liquid crystal.

[0054] The cross-linking agent described in step (2) is preferably at least one of genipin, glutaraldehyde and epichlorohydrin.

[0055] When the cross-linking agent is genipin, the pre-cross-linking time is preferably 2 to 72 hours; more preferably 10 to 48 hours; most preferably 2 to 12 hours.

[0056] When the cross-linking agent is glutaraldehyde, the pre-cross-linking time is preferably 0.2 to 24 hours; more preferably 5 to 20 hours; most preferably 9 to 15 hours.

[0057] When the cross-linking agent is epichlorohydrin, the pre-cross-linking time is preferably 0.1 to 48 hours; more preferably 2 to 36 hours; most preferably 8 to 10 hours.

[0058] The diameter of the copper rod described in step (3) is preferably 0.1 to 5 mm; more preferably 0.5 to 4 mm.

[0059] The radial freezing time in step (3) is preferably 0.2 to 6 hours; more preferably 0.5 to 5 hours.

[0060] The freeze-drying temperature in step (3) is preferably -40 to -10°C, and the time is preferably 4 to 24 hours.

[0061] The precursor solution in step (4) comprises the following components by mass percentage: 0.001% to 0.05% photoinitiator, 5% to 15% chitin whisker liquid crystal, 8% to 15% polyethylene glycol diacrylate, and 0.01% to 1% osteogenic and angiogenic active drug; preferably: 0.005% to 0.01% photoinitiator, 8% to 12% chitin whisker liquid crystal, 9% to 11% polyethylene glycol diacrylate, and 0.05% to 0.3% osteogenic and angiogenic active drug.

[0062] The photoinitiator is preferably at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate and 1-hydroxycyclohexyl phenyl ketone.

[0063] The weight average molecular weight of the polyethylene glycol diacrylate is preferably 200 to 10,000, and more preferably 200 to 5,000.

[0064] The osteogenic and angiogenic active drug is preferably at least one of bone morphogenetic protein, hypoxia inducible factor, vascular endothelial growth factor, transforming growth factor and deferoxamine.

[0065] The time of the photocrosslinking in step (4) is preferably 1 to 25 min; more preferably 5 to 20 min.

[0066] The cylindrical silicone mold described in step (5) is preferably 0.5 to 5 mm higher than the underlying bone repair scaffold material, and more preferably 1 to 3 mm higher.

[0067] The components of the precursor solution described in step (5) are as follows by mass percentage: 0.002% to 0.01% photoinitiator, 0.005% to 0.1% cartilage-promoting active drug, 4% to 10% chitin whisker liquid crystal, and 1% to 10% polyethylene glycol diacrylate; preferably as follows: 0.005% to 0.01% photoinitiator, 0.01% to 0.06% cartilage-promoting active drug, 5% to 8% chitin whisker liquid crystal, and 4% to 9% polyethylene glycol diacrylate.

[0068] The photoinitiator is preferably at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate and 1-hydroxycyclohexyl phenyl ketone.

[0069] The cartilage-promoting active drug is preferably at least one of insulin-like growth factor, baicalin, bone morphogenetic protein, human parathyroid hormone-related protein and transforming growth factor.

[0070] The weight average molecular weight of the polyethylene glycol diacrylate is preferably 200 to 10,000, and more preferably 200 to 5,000.

[0071] The time of the photocrosslinking in step (5) is preferably 1 to 25 minutes; more preferably 5 to 20 minutes.

[0072] Application of the above bionic bone / cartilage double-layer composite scaffold material in the preparation of biomedical products.

[0073] The biological application product is a bionic bone / cartilage repair scaffold.

[0074] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0075] 1. The present invention designs and prepares a bionic bone / cartilage double-layer composite scaffold material, wherein the lower layer is a scaffold material with bone-mimicking structural channels and loaded with vascularized drugs, and the upper layer is a liquid crystal hydrogel material loaded with cartilage-active drugs, which can realize the directional differentiation of stem cells into osteoblasts and chondrocytes.

[0076] 2. The uniquely designed radial freezing device of the present invention constructs a micron radial channel in the large transverse channel of the stent, which promotes the transport of nutrients and the migration of cells. The micron radial channel has good liquid crystal retention and gradient size distribution, which can promote cell recruitment, migration and adhesion.

[0077] 3. The mechanical properties of the composite liquid crystal hydrogel constructed by the present invention are easy to regulate and can maintain a liquid crystal state. At the same time, it can also achieve sustained release of drugs, thereby further regulating the differentiation of stem cells into cartilage and promoting the formation of vascularized bone.

[0078] 4. The bionic bone / cartilage double-layer composite scaffold material prepared by the present invention has excellent cell affinity, osteogenic / cartilage activity and angiogenic ability, and is expected to have good application prospects in the field of biomedical materials such as bone / cartilage tissue repair materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Figure 1 Schematic diagram of the structure of the double-layer stent material in Example 1 of the present invention.

[0080] Figure 2 These are the top view, side view and cross-sectional view of the 3D printed model and the real object in Example 2 of the present invention.

[0081] Figure 3The scanning electron microscope photograph of the micron radial channel in Example 3 of the present invention and the enlarged images of the proximal and distal ends thereof.

[0082] Figure 4 Polarized light microscope photographs and magnified images of the micron radial channel in Example 4 of the present invention, and circular dichroism spectra of the chitosan-chitin whisker liquid crystal precursor solution before and after cross-linking.

[0083] Figure 5 This is a cumulative release curve of deferoxamine and baicalin in Example 5 of the present invention.

[0084] Figure 6 This is a scanning electron microscope photograph of the interface between the upper cartilage repair hydrogel and the lower scaffold in Example 6 of the present invention.

[0085] Figure 7 It is the cyclic compression curve and partially enlarged curve diagram of the upper cartilage repair hydrogel in Example 7 of the present invention.

[0086] Figure 8 This is a laser confocal micrograph of mouse mesenchymal stem cells cultured for 24 hours on poly-L-lactic acid, drug-loaded or drug-free underlying bone repair scaffold material in Example 8 of the present invention.

[0087] Fig. 9 The graphs show the results of alkaline phosphatase staining (a) and quantitative analysis (d), type I collagen staining (b) and calcium nodule deposition staining (c) and quantitative analysis (e) of mouse mesenchymal stem cells on poly-L-lactic acid, drug-loaded or non-drug-loaded underlying bone repair scaffold materials in Example 9 of the present invention.

[0088] Fig.10 This is a graph showing the expression results of VEGF and HIF-1α of human umbilical vein endothelial cells in Example 10 of the present invention after being cultured for 5 days on poly-L-lactic acid, drug-loaded or drug-free lower layer bone repair scaffold materials.

[0089] Fig.11 This is a graph showing the expression results of Acan, Sox-9 and Col-II of mouse mesenchymal stem cells in Example 11 of the present invention after being cultured on polyethylene glycol diacrylate, drug-loaded or non-drug-loaded upper cartilage repair hydrogel for 7 days.

[0090] Fig.12 These are Alcian blue staining photos and quantitative analysis results of mouse mesenchymal stem cells cultured on polyethylene glycol diacrylate, drug-loaded or non-drug-loaded upper cartilage repair hydrogels in Example 12 of the present invention for 7 days. DETAILED DESCRIPTION

[0091] The present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be noted that the following embodiments are intended to facilitate the understanding of the present invention, but the embodiments of the present invention are not limited thereto. Based on the embodiments of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0092] Unless otherwise specified, all raw materials and reagents in the present invention are commercially available raw materials and reagents.

[0093] The preparation of the solution involved in the embodiment:

[0094] Chitosan solution: chitosan was dissolved in 2% acetic acid aqueous solution (chitosan was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number: C105801).

[0095] Genipin solution: Genipin (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., catalog number: G101204) was dissolved in deionized water.

[0096] Chitosan whisker liquid crystal: chitosan whiskers (chitosan raw materials were purchased from Shanghai MacLean Biochemical Technology Co., Ltd., item number: C769123, and then subjected to acid hydrolysis to obtain chitosan whiskers) were dispersed with deionized water and ultrasonically treated with a cell disruptor at a power of 450 W for 2 h.

[0097] The specific operation of acid hydrolysis treatment of chitosan raw materials is as follows: a certain amount of chitosan powder is added to a hydrochloric acid solution with a concentration of 3 mol / L, and boiled in a three-necked flask at 90°C under a nitrogen atmosphere for 3 hours; then, the reaction solution is centrifuged 3 times to remove excess acid and impurities, and then transferred to a dialysis bag with a molecular weight of 5000Da for dialyzation for three days; finally, the dialyzed sample is placed in a freeze dryer at -40 to -10°C for freeze drying, and the obtained sample is ground to obtain chitosan whiskers.

[0098] Recombinant human bone morphogenetic protein 2 solution: recombinant human bone morphogenetic protein 2 (purchased from MedChemExpress Biotechnology Company, product number: HY-P72854) was dissolved in deionized water.

[0099] Polyethylene glycol diacrylate solution: Dissolve polyethylene glycol diacrylate in deionized water.

[0100] Phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution: Phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number: L157759) was dissolved in deionized water.

[0101] Recombinant human insulin-like growth factor 1 solution: recombinant human insulin-like growth factor 1 (purchased from Yisheng Biotechnology (Shanghai) Co., Ltd., product number: 92211ES10) was dissolved in deionized water.

[0102] Human hypoxia-inducible factor-1α solution: human hypoxia-inducible factor-1α (Lianke Biotechnology, EK1392S) was dissolved in deionized water.

[0103] 1-Hydroxycyclohexylphenylmethylketone solution: 1-Hydroxycyclohexylphenylmethylketone (purchased from Shanghai Jizhi Biochemical Technology Co., Ltd., CAS: 947-19-3) was dissolved in deionized water.

[0104] Vascular endothelial growth factor A solution: Vascular endothelial growth factor A (purchased from MedChemExpress Biotechnology Company, product number: HY-P73473) was dissolved in deionized water.

[0105] Human parathyroid hormone-related protein solution: human parathyroid hormone-related protein (purchased from Shanghai Yanjin Biotechnology Co., Ltd., catalog number: F05609) was dissolved in deionized water to obtain

[0106] Glutaraldehyde solution: Glutaraldehyde (purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: G849973) was dissolved in deionized water.

[0107] Recombinant human transforming growth factor-β1 solution: recombinant human transforming growth factor-β1 (TGFbeta 1 / TGFβ1 protein, purchased from MedChemExpress Biotechnology Company, catalog number: HY-P7118) was dissolved in deionized water.

[0108] Deferioxamine solution: deferoxamine (purchased from MedChemExpress Biotechnology Company, product number: HY-B1625) was dissolved in deionized water.

[0109] Baicalin solution: Baicalin (purchased from MedChemExpress Biotechnology Company, product number: HY-N0197) was dissolved in deionized water.

[0110] Epichlorohydrin solution: epichlorohydrin (purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: E808937) was dissolved in deionized water.

[0111] Example 1

[0112] Step 1: Use polycaprolactone (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number: P579406, weight average molecular weight of 80,000 to 100,000) for fused deposition printing, set the nozzle extrusion temperature to 70°C, and the printing rate to 30 mm / min. The printed polycaprolactone stent has two layers of transverse large channels, each layer has 8 channels, and runs through the longitudinal large channels. The outer diameter range of the transverse large channel of the stent is 3 mm, and the inner diameter range is 0.8 mm; the diameter of the longitudinal large channel is 3 mm. Subsequently, 2g / L of dopamine (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number: D408026, the same below) reaction solution was prepared, and the polycaprolactone stent material was immersed in the dopamine reaction solution for 10 hours at a reaction temperature of 25°C. Finally, the reacted stent was vacuum dried to obtain a polydopamine-modified polycaprolactone stent material.

[0113] Step 2: Mix the chitosan solution, genipin solution and chitosan whisker liquid crystal to obtain a liquid crystal hydrogel precursor solution, wherein the content of each substance is 1% chitosan, 0.3% genipin, 7% chitosan whisker, and the remainder is solvent. The self-assembled liquid crystal precursor solution is injected into the transverse large channel of the stent for pre-crosslinking for 2 hours; then, a copper rod with a diameter of 3 mm is connected to a liquid nitrogen pool at one end and the other end is inserted into the longitudinal large channel of the stent for radial freezing for 0.5 hours, followed by freeze drying at -20°C for 6 hours to obtain a stent with micron radial channels.

[0114] Step 3: Mix recombinant human bone morphogenetic protein 2 solution, polyethylene glycol diacrylate (average molecular weight of ~600) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution, wherein the content of each substance is calculated by mass percentage as follows: 0.05% recombinant human bone morphogenetic protein 2, 10% polyethylene glycol diacrylate, 0.005% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 9% chitin whisker, and the remainder is solvent. The precursor solution is poured into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light at a wavelength of 365nm for 5 minutes.

[0115] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 1 mm higher, mix the recombinant human insulin-like growth factor 1 solution, polyethylene glycol diacrylate (average molecular weight of ~600) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution, and chitin whisker liquid crystal to obtain a liquid crystal precursor solution, in which the content of each substance is calculated by mass percentage as follows: 0.05% recombinant human insulin-like growth factor 1, 5% polyethylene glycol diacrylate, 0.005% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 5% chitin whisker, and the remainder is solvent. Inject the liquid crystal precursor solution into the upper mold, use ultraviolet light with a wavelength of 365nm for cross-linking for 5 minutes, and demold after complete cross-linking to obtain the following. Figure 1 The bionic bone / cartilage double-layer composite scaffold material shown.

[0116] Example 2

[0117] Step 1: Use L-lactic acid (weight average molecular weight of 200,000, purchased from Shenzhen Jusheng Biotechnology Co., Ltd.) for fused deposition printing, set the nozzle extrusion temperature to 200°C, and the printing rate to 50 mm / min. Figure 2 As shown, the printed polylactic acid scaffold has two layers of transverse channels, each layer has 8 channels, and runs through the longitudinal channels. The outer diameter of the transverse channel of the scaffold is 2.5 mm, the inner diameter is 0.8 mm, and the diameter of the longitudinal channel is 3 mm. Subsequently, a 2g / L dopamine reaction solution was prepared, and the polylactic acid scaffold material was immersed in the reaction solution for 5 hours at a reaction temperature of 20°C. Finally, the scaffold after the reaction was vacuum dried to obtain a polydopamine-modified polylactic acid scaffold material.

[0118] Step 2: Mix the chitosan solution, genipin solution and chitosan whisker liquid crystal to obtain a liquid crystal hydrogel precursor solution, wherein the content of each substance is calculated by mass percentage as follows: chitosan 1.5%, genipin 0.3%, chitosan whisker 9%, and solvent balance. The self-assembled liquid crystal precursor solution is injected into the transverse large channel of the stent for pre-crosslinking for 12 hours; then, a copper rod with a diameter of 2.5 mm is connected to a liquid nitrogen pool at one end and the other end is inserted into the longitudinal large channel of the stent for radial freezing for 1 hour, followed by freeze drying at -15°C for 7 hours, and freeze drying to obtain a stent with micron radial channels.

[0119] Step 3: Mix the human hypoxia-inducible factor-1α solution, polyethylene glycol diacrylate (weight average molecular weight 2000) solution, 1-hydroxycyclohexyl phenyl ketone solution, and chitin whisker liquid crystal to prepare a liquid crystal precursor solution, wherein the content of each substance is calculated by mass percentage as follows: 0.5% human hypoxia-inducible factor-1α, 9% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone, 8% chitin whisker, and the remainder is solvent. The precursor solution is poured into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light at a wavelength of 365nm for 10 minutes.

[0120] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 1 mm higher, mix the recombinant human bone morphogenetic protein 2 solution, polyethylene glycol diacrylate (weight average molecular weight is 2000) solution, 1-hydroxycyclohexyl phenyl ketone solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution, wherein the content of each substance is calculated by mass percentage as follows: 0.02% recombinant human bone morphogenetic protein 2, 7% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone, 7% chitin whisker, and the remainder is solvent. Inject the liquid crystal precursor solution into the upper mold, use ultraviolet light with a wavelength of 365nm for cross-linking for 10 minutes, and demould after complete cross-linking to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0121] Example 3

[0122] Step 1: Use left-handed polylactic acid (weight average molecular weight of 100,000) for fused deposition printing, set the nozzle extrusion temperature to 180°C, and the printing rate to 40 mm / min. The printed polylactic acid stent has two layers of transverse large channels, each layer has 8 channels, and penetrates the longitudinal large channels. The outer diameter range of the transverse large channel of the stent is 2.5 mm, and the inner diameter range is 0.7 mm; the diameter of the longitudinal large channel is 3 mm. Subsequently, 2g / L of dopamine reaction solution was prepared, and the polylactic acid stent material was immersed in the reaction solution for 10 hours at a reaction temperature of 25°C. Finally, the reacted stent was vacuum dried to obtain a polydopamine-modified polylactic acid stent material.

[0123] Step 2: Mix the chitosan solution, genipin solution and chitosan whisker liquid crystal to obtain a liquid crystal hydrogel precursor solution, in which the content of each substance is calculated by mass percentage as follows: 2% chitosan, 0.3% genipin, 10% chitosan whisker, and the remainder is solvent. The self-assembled liquid crystal precursor solution is injected into the large transverse channels of the stent for pre-crosslinking for 12 hours; then, a copper rod with a diameter of 2.5 mm is connected to a liquid nitrogen pool at one end and the other end is inserted into the large longitudinal channel of the stent for radial freezing for 2 hours, followed by freeze drying at -20°C for 11 hours to obtain a stent with micron radial channels. Figure 3As shown in the figure, the scanning electron microscope photo shows that the micron radial channels are arranged neatly and orderly in the large channel, the channel structure is complete, and it presents a gradient orientation structure. In terms of size, the distal dimension of the micron radial channel is larger than the proximal dimension, which may be conducive to the recruitment and migration of cells.

[0124] Step 3: Mix vascular endothelial growth factor A solution, polyethylene glycol diacrylate (weight average molecular weight of 2000) solution, 1-hydroxycyclohexyl phenyl ketone solution and chitosan whisker liquid crystal to obtain a liquid crystal precursor solution, wherein the content of each substance is by mass percentage: 0.2% vascular endothelial growth factor A, 10% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone and 9% chitosan whisker, and the remainder is solvent. The precursor solution is perfused into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light of a wavelength of 365nm for 5 minutes.

[0125] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 2 mm higher, mix human parathyroid hormone related protein solution, polyethylene glycol diacrylate (weight average molecular weight is 2000) solution, 1-hydroxycyclohexyl phenyl ketone solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution, wherein the content of each substance is calculated by mass percentage: 0.01% human parathyroid hormone related protein, 6% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone and 7% chitin whisker, and the remainder is solvent. Inject the liquid crystal precursor solution into the upper mold, use ultraviolet light with a wavelength of 365nm for cross-linking for 5 minutes, and demould after complete cross-linking to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0126] Example 4

[0127] Step 1: Use left-handed polylactic acid (weight average molecular weight of 200,000) for fused deposition printing, set the nozzle extrusion temperature to 185°C, and the printing rate to 45 mm / min. The printed polylactic acid stent has two layers of transverse large channels, each layer has 4 channels, and penetrates the longitudinal large channels. The outer diameter range of the transverse large channel of the stent is 3 mm, and the inner diameter range is 0.5 mm; the diameter of the longitudinal large channel is 3 mm. Subsequently, a 1g / L dopamine reaction solution was prepared, and the polylactic acid stent material was immersed in the reaction solution for 8 hours at a reaction temperature of 20°C. Finally, the reacted stent was vacuum dried to obtain a polydopamine-modified polylactic acid stent material.

[0128] Step 2: Mix the chitosan solution, glutaraldehyde solution, and chitosan whisker liquid crystal to obtain a liquid crystal hydrogel precursor solution, in which the content of each substance is, by mass percentage, 1% chitosan, 0.1% glutaraldehyde, and 8% chitosan whiskers, with the remainder being solvent. Inject the self-assembled liquid crystal precursor solution into the large transverse channels of the stent for pre-crosslinking for 15 hours; then, connect one end of a 3 mm diameter copper rod to a liquid nitrogen pool and the other end to the large longitudinal channel of the stent for radial freezing for 1.5 hours, followed by freeze drying at -25°C for 10 hours to obtain a stent with micron radial channels. Figure 4 As shown in the figure, through polarizing microscope observation, we found that the micron radial channel showed a colorful liquid crystal texture, which is a typical feature of cholesteric liquid crystal. Then, through circular dichroism testing, we found that the micron radial channel also had chiral characteristics. Based on the above conclusions, the micron radial channel is considered to have a good cholesteric liquid crystal texture.

[0129] Step 3: Mix recombinant human transforming growth factor-β1 solution, polyethylene glycol diacrylate (weight average molecular weight of 1000) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution, wherein the content of each substance is calculated by mass percentage as follows: 0.1% recombinant human transforming growth factor-β1, 10% polyethylene glycol diacrylate, 0.01% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 10% chitin whisker, and the remainder is solvent. The precursor solution is poured into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light at a wavelength of 365nm for 10 minutes.

[0130] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 1.5 mm higher, mix the recombinant human transforming growth factor-β1 solution, polyethylene glycol diacrylate (weight average molecular weight of 1000) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution, wherein the content of each substance is calculated by mass percentage: 0.01% recombinant human transforming growth factor-β1, 8% polyethylene glycol diacrylate, 0.01% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 7% chitin whisker, and the rest is solvent. Inject the liquid crystal precursor solution into the upper mold, use ultraviolet light with a wavelength of 365nm for cross-linking for 5 minutes, and demold after complete cross-linking to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0131] Example 5

[0132] Step 1: Use polyetheretherketone (weight average molecular weight of 50,000, purchased from Shenzhen Jusheng Biotechnology Co., Ltd.) for fused deposition printing, set the nozzle extrusion temperature to 350°C, and the printing rate to 40 mm / min. The printed polyetheretherketone scaffold has two layers of transverse large channels, each layer has 6 channels, and penetrates the longitudinal large channels. The outer diameter range of the transverse large channel of the scaffold is 3 mm, and the inner diameter range is 0.5 mm; the diameter of the longitudinal large channel is 4 mm. Subsequently, a 1.5 g / L dopamine reaction solution was prepared, and the polyetheretherketone scaffold material was immersed in the reaction solution for 12 hours at a reaction temperature of 25°C. Finally, the reacted scaffold was vacuum dried to obtain a polydopamine-modified polyetheretherketone scaffold material.

[0133] Step 2: Mix chitosan solution, glutaraldehyde solution and chitin whisker liquid crystal to obtain liquid crystal hydrogel precursor solution, wherein the content of each substance is 3% chitosan, 0.4% glutaraldehyde, 9% chitin whisker, and the rest is solvent. Inject the self-assembled liquid crystal precursor solution into the transverse large channel of the stent for pre-crosslinking for 15 hours; then, connect one end of a 4 mm diameter copper rod to a liquid nitrogen pool, and insert the other end into the longitudinal large channel of the stent, perform radial freezing for 4 hours, and then freeze-dry at -30°C for 14 hours to obtain a stent with micron radial channels.

[0134] Step 3: Mix the deferoxamine solution, polyethylene glycol diacrylate (weight average molecular weight of 1000) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 0.1% deferoxamine, 10% polyethylene glycol diacrylate, 0.01% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate and 8% chitin whisker, and the remainder is solvent. Subsequently, the precursor solution is perfused into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light at a wavelength of 365nm for 10 minutes.

[0135] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 1 mm higher, mix baicalin solution, polyethylene glycol diacrylate (weight average molecular weight of 1000) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; the content of each substance is calculated by mass percentage: 0.02% baicalin, 6% polyethylene glycol diacrylate, 0.01% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 7% chitin whisker, and the rest is solvent. Inject the liquid crystal precursor solution into the upper mold, use ultraviolet light with a wavelength of 365nm for cross-linking for 5 minutes, and demold after complete cross-linking to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0136] like Figure 5As shown, the release behavior of the two drugs in the material was tested. Both deferoxamine and baicalin showed rapid release behavior in the early stage, and then slowed down. Finally, the cumulative release rates of deferoxamine and baicalin could reach 75.6% and 82.5%, respectively.

[0137] Example 6

[0138] Step 1: Use left-handed polylactic acid (weight average molecular weight of 200,000) for fused deposition printing, set the nozzle extrusion temperature to 200°C, and the printing rate to 45 mm / min. The printed polylactic acid stent has two layers of transverse large channels, each layer has 8 channels, and penetrates the longitudinal large channels. The outer diameter range of the transverse large channel of the stent is 3 mm, and the inner diameter range is 0.8 mm; the diameter of the longitudinal large channel is 3 mm. Subsequently, 2g / L of dopamine reaction solution was prepared, and the polylactic acid stent material was immersed in the reaction solution for 15 hours at a reaction temperature of 20°C. Finally, the reacted stent was vacuum dried to obtain a polydopamine-modified polylactic acid stent material.

[0139] Step 2: Mix the chitosan solution, epichlorohydrin solution and chitosan whisker liquid crystal to obtain a liquid crystal hydrogel precursor solution; the content of each substance is calculated by mass percentage as follows: 2% chitosan, 0.2% epichlorohydrin, 8% chitosan whisker, and the remainder is solvent. The liquid crystal precursor solution is injected into the transverse large channel of the stent for pre-crosslinking for 10 hours; then, one end of a copper rod with a diameter of 3 mm is connected to a liquid nitrogen pool, and the other end is inserted into the longitudinal large channel of the stent, and radial freezing is performed for 3 hours, followed by freeze drying at -30°C for 15 hours to obtain a stent with micron radial channels.

[0140] Step 3: Mix the deferoxamine solution, polyethylene glycol diacrylate (weight average molecular weight of 5000) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 0.2% deferoxamine, 10% polyethylene glycol diacrylate, 0.01% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 10% chitin whisker, and the remainder is solvent. The precursor solution is poured into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light at a wavelength of 365nm for 12 minutes.

[0141] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 1 mm higher, mix baicalin solution, polyethylene glycol diacrylate (weight average molecular weight of 5000) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker solution to obtain a liquid crystal precursor solution; the content of each substance is calculated by mass percentage: 0.05% baicalin, 8% polyethylene glycol diacrylate, 0.008% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 8% chitin whisker, and the rest is solvent. Inject the liquid crystal precursor solution into the upper mold, use ultraviolet light with a wavelength of 365nm for cross-linking for 12 minutes, and demold after complete cross-linking to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0142] The interfacial bonding properties between the upper hydrogel layer and the lower scaffold material of the double-layer scaffold material were observed by scanning electron microscopy. Figure 6 As shown, there is no obvious crack or detachment between the upper and lower layers, which indicates that the prepared double-layer bone / cartilage scaffold material has good interface bonding properties.

[0143] Example 7

[0144] Step 1: Use polyetheretherketone (weight average molecular weight of 70,000) for fused deposition printing, set the nozzle extrusion temperature to 360°C, and the printing rate to 45 mm / min. The printed polyetheretherketone stent has two layers of transverse large channels, each layer has 8 channels, and penetrates the longitudinal large channels. The outer diameter range of the transverse large channel of the stent is 3 mm, and the inner diameter range is 1 mm; the diameter of the longitudinal large channel is 3 mm. Subsequently, 2g / L of dopamine reaction solution was prepared, and the polyetheretherketone stent material was immersed in the reaction solution for 15 hours at a reaction temperature of 20°C. Finally, the reacted stent was vacuum dried to obtain a polydopamine-modified polyetheretherketone stent material.

[0145] Step 2: Mix the chitosan solution, epichlorohydrin solution and chitosan whisker liquid crystal to obtain a liquid crystal hydrogel precursor solution; the content of each substance is calculated by mass percentage as follows: 2% chitosan, 0.2% epichlorohydrin, 8% chitosan whisker, and the remainder is solvent. The liquid crystal precursor solution is injected into the transverse large channel of the stent for pre-crosslinking for 10 hours; then, a copper rod with a diameter of 3 mm is connected to a liquid nitrogen pool at one end and the other end is inserted into the longitudinal large channel of the stent for radial freezing for 3 hours, followed by freeze drying at -35°C for 16 hours to obtain a stent with micron radial channels.

[0146] Step 3: Mix the deferoxamine solution, polyethylene glycol diacrylate (weight average molecular weight of 3000) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 0.2% deferoxamine, 10% polyethylene glycol diacrylate, 0.01% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 10% chitin whisker, and the remainder is solvent. The precursor solution is poured into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light at a wavelength of 365nm for 8 minutes.

[0147] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 1 mm higher, mix baicalin solution, polyethylene glycol diacrylate (weight average molecular weight of 3000) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; the content of each substance is 0.05% baicalin, 8% polyethylene glycol diacrylate, 0.01% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 8% chitin whisker, and the rest is solvent. Inject the liquid crystal precursor solution into the upper mold, use ultraviolet light with a wavelength of 365nm for cross-linking for 8 minutes, and demold after complete cross-linking to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0148] like Figure 7 As shown in the figure, the mechanical properties of the upper cartilage hydrogel were evaluated by compression cycle test, and a cylindrical hydrogel with a diameter of 10 mm and a height of 4 mm was selected for testing. After more than 1,000 compressions, the hydrogel can still maintain its original strength without obvious attenuation. This result shows that the prepared hydrogel has good compressive resistance and mechanical stability.

[0149] Example 8

[0150] Step 1: Use left-handed polylactic acid (weight average molecular weight of 300,000) for fused deposition printing, set the nozzle extrusion temperature to 210°C, and the printing rate to 40 mm / min. The printed polylactic acid stent has two layers of transverse large channels, each layer has 6 channels, and penetrates the longitudinal large channels. The outer diameter range of the transverse large channel of the stent is 3 mm, and the inner diameter range is 2 mm; the diameter of the longitudinal large channel is 3 mm. Subsequently, a 1.5 g / L dopamine reaction solution was prepared, and the polylactic acid stent material was immersed in the reaction solution for 12 hours at a reaction temperature of 15°C. Finally, the reacted stent was vacuum dried to obtain a polydopamine-modified polylactic acid stent material.

[0151] Step 2: Mix chitosan solution, glutaraldehyde solution and chitin whisker liquid crystal to obtain liquid crystal hydrogel precursor solution; the content of each substance is calculated by mass percentage as follows: 1.5% chitosan, 0.2% glutaraldehyde, 8.5% chitin whisker, and the remainder is solvent. The self-assembled liquid crystal precursor solution is injected into the transverse large channel of the stent for pre-crosslinking for 12 hours; then, a copper rod with a diameter of 3 mm is connected to a liquid nitrogen pool at one end and the other end is inserted into the longitudinal large channel of the stent for radial freezing for 4.5 hours, followed by freeze drying at -40°C for 16 hours to obtain a stent with micron radial channels.

[0152] Step 3: Mix the deferoxamine solution, polyethylene glycol diacrylate (weight average molecular weight of 800) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 0.2% deferoxamine, 9% polyethylene glycol diacrylate, 0.01% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 10% chitin whisker, and the remainder is solvent. The precursor solution is poured into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light at a wavelength of 365nm for 12 minutes.

[0153] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 1 mm higher, mix human parathyroid hormone-related protein solution, polyethylene glycol diacrylate (weight average molecular weight of 600) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; the content of each substance is calculated by mass percentage: 0.05% human parathyroid hormone-related protein, 8% polyethylene glycol diacrylate, 0.01% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 8% chitin whisker, and the rest is solvent. Inject the liquid crystal precursor solution into the upper mold, use ultraviolet light with a wavelength of 365nm for cross-linking for 12 minutes, and demold after complete cross-linking to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0154] Pure L-polylactic acid scaffold material was selected as the control group, and L-polylactic acid with a weight average molecular weight of 300,000 was used for fused deposition printing. The nozzle extrusion temperature was set to 210°C and the printing rate was 40 mm / min. The printed polylactic acid scaffold has two layers of transverse large channels, each layer has 6 channels, and runs through the longitudinal large channels. The outer diameter range of the transverse large channel of the scaffold is 3 mm, the inner diameter range is 2 mm; the diameter of the longitudinal large channel is 3 mm. At the same time, the deferoxamine solution, polyethylene glycol diacrylate (weight average molecular weight of 800) solution, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution and chitin whisker liquid crystal were mixed to obtain a liquid crystal precursor solution, in which the content of each substance is calculated by mass percentage: 0.2% deferoxamine, 9% polyethylene glycol diacrylate, 0.01% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 10% chitin whisker, and solvent balance. The precursor solution was perfused into the longitudinal large channel, and after photo-crosslinking for 12 minutes, a lower layer bone repair scaffold material without osteogenic and angiogenic drugs was obtained.

[0155] The above three groups of scaffold materials were prepared into cylinders with a diameter of 15 mm and a height of 4 mm, and mouse mesenchymal stem cells (purchased from Saiye (Guangzhou) Biotechnology Co., Ltd., catalog number: MUBMX-01001) were cultured. The cells were placed in a 25 cm 2 Place in tissue culture flask at 37°C and 5% CO 2 The cells were cultured in an incubator with a relative humidity of 95% and a concentration of 10%. The culture medium used in the cell culture process was a complete culture medium containing 10% fetal bovine serum (purchased from Gibco Co., Ltd., USA, item number: 26170035), 1% double antibody (purchased from Gibco Co., Ltd., USA, item number: 15140148) and 89% DMEM (purchased from Gibco Co., Ltd., USA, item number: 11965092). The cell culture medium needs to be changed every other day. The sterilized scaffold sample with a diameter of 15 mm was placed in a 24-well plate and the cells were cultured at a rate of 1×10 4 The cells / well were seeded onto the plate at a density of 1:1 and three sets of parallel samples were set up.

[0156] After 48 hours of culture, rhodamine-labeled phalloidin (purchased from Gibco Co., Ltd., USA, catalog number: A12379) and 4',6-diamidino-2-phenylindole (purchased from Gibco Co., Ltd., USA, catalog number: D1306) were used to observe the cell morphology. Figure 8 As shown, the morphology of bone marrow mesenchymal stem cells on the scaffold material was observed by laser confocal microscopy. Compared with the polylactic acid scaffold, the construction of micron radial channels and the introduction of angiogenic drugs enhanced the expression and spreading area of ​​the actin filaments of the stem cells, confirming its excellent cell affinity.

[0157] Example 9

[0158] Step 1: Use left-handed polylactic acid (weight average molecular weight of 300,000) for fused deposition printing, set the nozzle extrusion temperature to 220°C, and the printing rate to 40 mm / min. The printed polylactic acid stent has three layers of transverse large channels, with 8 channels in each layer, and penetrates the longitudinal large channels. The outer diameter range of the transverse large channel of the stent is 2.5 mm, and the inner diameter range is 0.4 mm; the diameter of the longitudinal large channel is 0.5 mm. Subsequently, 4g / L of dopamine reaction solution was prepared, and the polylactic acid stent material was immersed in the reaction solution for 24 hours at a reaction temperature of 30°C. Finally, the reacted stent was vacuum dried to obtain a polydopamine-modified polylactic acid stent material.

[0159] Step 2: Mix chitosan solution, glutaraldehyde solution and chitosan whisker liquid crystal to obtain liquid crystal hydrogel precursor solution; the content of each substance is calculated by mass percentage as follows: 5% chitosan, 0.5% glutaraldehyde and 12% chitosan whisker, and the remainder is solvent. The liquid crystal precursor solution is injected into the transverse large channel of the stent for pre-crosslinking for 12 hours; then, one end of a copper rod with a diameter of 0.5 mm is connected to a liquid nitrogen pool, and the other end is inserted into the longitudinal large channel of the stent, and radial freezing is performed for 5 hours, followed by freeze drying at -10°C for 12 hours to obtain a stent with micron radial channels.

[0160] Step 3: Mix the deferoxamine solution, polyethylene glycol diacrylate (weight average molecular weight 4000) solution, 1-hydroxycyclohexyl phenyl ketone solution and chitosan whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 0.2% deferoxamine, 9% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone, 12% chitosan whisker, and the remainder is solvent. The precursor solution is poured into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light at a wavelength of 365nm for 20 minutes.

[0161] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 3 mm higher, mix recombinant human transforming growth factor-β1 solution, polyethylene glycol diacrylate (weight average molecular weight of 4000), 1-hydroxycyclohexyl phenyl ketone and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage: 0.05% recombinant human transforming growth factor-β1, 8% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone, 7% chitin whisker, and the remainder is solvent. Inject the liquid crystal precursor solution into the upper mold and use ultraviolet light with a wavelength of 365nm for cross-linking for 20 minutes. After complete cross-linking, demoulding is performed to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0162] Pure L-polylactic acid scaffold material was selected as the control group, and L-polylactic acid with a weight average molecular weight of 300,000 was used for fused deposition printing. The nozzle extrusion temperature was set to 220°C and the printing rate was 40 mm / min. The printed polylactic acid scaffold has three layers of transverse large channels, with 8 channels in each layer, and runs through the longitudinal large channels. The outer diameter range of the transverse large channel of the scaffold is 2.5 mm, the inner diameter range is 0.4 mm; the diameter of the longitudinal large channel is 0.5 mm. At the same time, a polyethylene glycol diacrylate solution with a weight average molecular weight of 4000, a 1-hydroxycyclohexyl phenyl ketone solution and a chitin whisker liquid crystal were mixed to obtain a liquid crystal precursor solution; the content of each substance, by mass percentage, is: 9% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone, 12% chitin whiskers, and the solvent balance. The precursor solution was perfused into the longitudinal large channel, and after cross-linking with ultraviolet light at a wavelength of 365 nm for 20 minutes, a lower layer bone repair scaffold material without osteogenic and angiogenic drugs was obtained.

[0163] The three groups of scaffold materials were prepared into cylinders with a diameter of 15 mm and a height of 4 mm, and mouse mesenchymal stem cells were cultured (same as in Example 8). Fig. 9 As shown, by monitoring the alkaline phosphatase, type I collagen and calcium nodules secreted by stem cells on the scaffold, we found that compared with the polylactic acid scaffold, the construction of micron radial channels and the introduction of angiogenic drugs enhanced the osteogenic differentiation ability of stem cells in the early, middle and late stages.

[0164] Example 10

[0165] Step 1: Use left-handed polylactic acid (weight average molecular weight of 150,000) for fused deposition printing, set the nozzle extrusion temperature to 195°C, and the printing rate to 35 mm / min. The printed polylactic acid stent has two layers of transverse large channels, each layer has 5 channels, and penetrates the longitudinal large channels. The outer diameter range of the transverse large channel of the stent is 2.5 mm, and the inner diameter range is 0.5 mm; the diameter of the longitudinal large channel is 2.5 mm. Subsequently, 2.5 g / L of dopamine reaction solution was prepared, and the polylactic acid stent material was immersed in the reaction solution for 16 hours at a reaction temperature of 15°C. Finally, the reacted stent was vacuum dried to obtain a polydopamine-modified polylactic acid stent material.

[0166] Step 2: Mix chitosan solution, glutaraldehyde solution and chitosan whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 2.5% chitosan, 0.1% glutaraldehyde, 11% chitosan whisker, and the remainder is solvent. The liquid crystal precursor solution is injected into the transverse large channel of the stent for pre-crosslinking for 9 hours; then, one end of a copper rod with a diameter of 2.5 mm is connected to a liquid nitrogen pool, and the other end is inserted into the longitudinal large channel of the stent, and radial freezing is performed for 4.5 hours, followed by freeze drying at -20°C for 12 hours to obtain a stent with micron radial channels.

[0167] Step 3: Mix the deferoxamine solution, polyethylene glycol diacrylate (weight average molecular weight of 200) solution, 1-hydroxycyclohexyl phenyl ketone solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 0.3% deferoxamine, 11% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone, 12% chitin whisker, and the remainder is solvent. The precursor solution is poured into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light of a wavelength of 365nm for 8 minutes.

[0168] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 1.5 mm higher, mix the recombinant human transforming growth factor-β1 solution, polyethylene glycol diacrylate (weight average molecular weight is 200) solution, 1-hydroxycyclohexyl phenyl ketone solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage: 0.06% recombinant human transforming growth factor-β1, 4% polyethylene glycol diacrylate, 0.008% 1-hydroxycyclohexyl phenyl ketone, 7% chitin whisker, and the remainder is solvent. The liquid crystal precursor solution is injected into the upper mold and cross-linked with ultraviolet light of a wavelength of 365nm for 8 minutes. After complete cross-linking, demoulding is performed to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0169] Pure L-polylactic acid scaffold material was selected as the control group, and L-polylactic acid with a weight average molecular weight of 150,000 was used for fused deposition printing. The nozzle extrusion temperature was set to 195°C and the printing rate was 35 mm / min. The printed polylactic acid scaffold has two layers of transverse large channels, each layer has 5 channels, and runs through the longitudinal large channels. The outer diameter range of the transverse large channel of the scaffold is 2.5 mm, and the inner diameter range is 0.5 mm; the diameter of the longitudinal large channel is 2.5 mm. At the same time, a polyethylene glycol diacrylate solution with a weight average molecular weight of 200, a 1-hydroxycyclohexyl phenyl ketone solution and a chitin whisker liquid crystal were mixed to obtain a liquid crystal precursor solution; wherein the content of each substance is 11% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone and 12% chitin whiskers by mass percentage, and the solvent is the remainder. The precursor solution was perfused into the longitudinal large channel, and after cross-linking with ultraviolet light at a wavelength of 365 nm for 8 minutes, a lower layer bone repair scaffold material without osteogenic and vascularizing drugs was obtained.

[0170] The three groups of scaffold materials were prepared into cylinders with a diameter of 15 mm and a height of 4 mm, and human umbilical vein endothelial cells (purchased from Beijing Bio-Bowei Biotechnology Co., Ltd., catalog number: bio-105890) were cultured in the same manner as in Example 8. Fig.10As shown, by detecting the angiogenic markers of human umbilical vein endothelial cells on the stent (using reverse transcription PCR technology to detect the expression of angiogenic-related genes of human umbilical vein endothelial cells, with GAPDH as the internal reference, the reaction conditions are: 94°C for 5 minutes, 50°C for 2 minutes, 72°C for 5 minutes, a total of 30 cycles (primer sequences are shown in Table 1 below), we found that the introduction of angiogenic drugs can enhance the angiogenic ability of the stent material.

[0171] Table 1 Primer sequences of angiogenic genes

[0172] Primers Forward sequencing (5'-3') Reverse sequencing (3'-5') Vascular endothelial growth factor GCAGATTATGCGGATCAAACC TTTCGTTTTTGCCCCTTTCC Hypoxia-inducible factor GTGGATTACCACAGCTGA GCTCAGTTAACTTGATCCA

[0173] Embodiment 11

[0174] Step 1: Use left-handed polylactic acid (weight average molecular weight of 200,000) for fused deposition printing, set the nozzle extrusion temperature to 205°C, and the printing rate to 40 mm / min. The printed polylactic acid stent has three layers of transverse large channels, each layer has 8 channels, and penetrates the longitudinal large channels. The outer diameter range of the transverse large channel of the stent is 2 mm, and the inner diameter range is 0.5 mm; the diameter of the longitudinal large channel is 3 mm. Subsequently, 3g / L of dopamine reaction solution was prepared, and the polylactic acid stent material was immersed in the reaction solution for 18 hours at a reaction temperature of 30°C. Finally, the reacted stent was vacuum dried to obtain a polydopamine-modified polylactic acid stent material.

[0175] Step 2: Mix the chitosan solution, epichlorohydrin solution and chitosan whisker liquid crystal to obtain a liquid crystal hydrogel precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 4% chitosan, 0.4% epichlorohydrin, 10% chitosan whisker, and the remainder is solvent. The self-assembled liquid crystal precursor solution is injected into the transverse large channel of the stent for pre-crosslinking for 10 hours; then, a copper rod with a diameter of 3 mm is connected to a liquid nitrogen pool at one end and the other end is inserted into the longitudinal large channel of the stent for radial freezing for 3.5 hours, followed by freeze drying at -20°C for 12 hours to obtain a stent with micron radial channels.

[0176] Step 3: Mix recombinant human transforming growth factor-β1 solution, polyethylene glycol diacrylate (weight average molecular weight is 2000) solution, 1-hydroxycyclohexyl phenyl ketone solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 0.2% recombinant human transforming growth factor-β1, 9% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone, 10% chitin whisker, and the remainder is solvent. The precursor solution is poured into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light of a wavelength of 365nm for 8 minutes.

[0177] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 2 mm higher, mix baicalin solution, polyethylene glycol diacrylate solution with a weight average molecular weight of 2000, 1-hydroxycyclohexyl phenyl ketone solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is 0.05% baicalin, 8% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone, 8% chitin whisker, and the remainder is solvent. Inject the liquid crystal precursor solution into the upper mold and use ultraviolet light with a wavelength of 365nm for cross-linking for 8 minutes. After complete cross-linking, demoulding is performed to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0178] Pure polyethylene glycol diacrylate hydrogel was selected as the control group, and a precursor solution containing 8% polyethylene glycol diacrylate with a weight average molecular weight of 2000 and 0.01% 1-hydroxycyclohexyl phenyl ketone was prepared according to the mass fraction, injected into the upper mold, and crosslinked for 8 minutes using ultraviolet light with a wavelength of 365nm. After complete crosslinking, the upper cartilage repair hydrogel material was demoulded. At the same time, a polyethylene glycol diacrylate solution with a weight average molecular weight of 2000, a 1-hydroxycyclohexyl phenyl ketone solution and a chitin whisker liquid crystal were mixed to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 8% polyethylene glycol diacrylate with a weight average molecular weight of 2000, 0.01% 1-hydroxycyclohexyl phenyl ketone, 8% chitin whiskers, and the remainder is solvent. The liquid crystal precursor solution is injected into the upper mold and cross-linked using ultraviolet light with a wavelength of 365 nm for 8 minutes. After complete cross-linking, the upper cartilage repair hydrogel material without encapsulating cartilage drugs is obtained by demolding.

[0179] The three groups of hydrogel materials were prepared into cylinders with a diameter of 10 mm and a height of 2 mm, and mouse mesenchymal stem cells were cultured (same as in Example 8). Fig.11 As shown, by detecting the chondrogenic differentiation markers of mesenchymal stem cells on the upper hydrogel (using reverse transcription PCR technology to detect the expression of chondrogenic related genes of mouse mesenchymal stem cells, GAPDH was used as the internal reference, and the reaction conditions were: 94°C for 5 minutes, 50°C for 2 minutes, 72°C for 5 minutes, a total of 30 cycles (primer sequences are shown in Table 2 below), we found that chitin whisker liquid crystals can promote the expression of aggrecan (ACAN), Y chromosome sex determining region transcription factor 9 (SOX-9) and type II collagen (COL-II), and the introduction of baicalin further promoted the secretion of ACAN and COL-II. The above results show that the introduction of chitin whisker liquid crystals and baicalin has a certain synergistic effect in promoting the chondrogenic differentiation of stem cells.

[0180] Table 2 Primer sequences of cartilage forming genes

[0181] Primers Forward sequencing (5'-3') Reverse sequencing (3'-5') Aggrecan CTAGCTGCTTAGCAGGGATAACG AACCTTCGCTTCCATACTCG SOX-9 AGCGAACGCACATCAAGA GCTGCGTGACTGTAGTAGGA Type II collagen GCAAGACCGTCATCGAGTA AAGCAGACAGGCCCTATGT

[0182] Example 12

[0183] Step 1: Use left-handed polylactic acid (weight average molecular weight of 200,000) for fused deposition printing, set the nozzle extrusion temperature to 205°C, and the printing rate to 40 mm / min. The printed polylactic acid stent has three layers of transverse large channels, each layer has 8 channels, and penetrates the longitudinal large channels. The outer diameter range of the transverse large channel of the stent is 2 mm, and the inner diameter range is 0.5 mm; the diameter of the longitudinal large channel is 3 mm. Subsequently, 3g / L of dopamine reaction solution was prepared, and the polylactic acid stent material was immersed in the reaction solution for 18 hours at a reaction temperature of 30°C. Finally, the reacted stent was vacuum dried to obtain a polydopamine-modified polylactic acid stent material.

[0184] Step 2: Mix chitosan solution, epichlorohydrin solution and chitosan whisker liquid crystal to obtain liquid crystal hydrogel precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 3.5% chitosan, 0.5% epichlorohydrin, 8% chitosan whisker, and the remainder is solvent. The self-assembled liquid crystal precursor solution is injected into the transverse large channel of the stent for pre-crosslinking for 8 hours; then, a copper rod with a diameter of 3 mm is connected to a liquid nitrogen pool at one end and the other end is inserted into the longitudinal large channel of the stent for radial freezing for 5 hours, and then freeze-dried at -15°C for 20 hours to obtain a stent with micron radial channels.

[0185] Step 3: Mix the recombinant human transforming growth factor-β1 solution, the polyethylene glycol diacrylate solution with a weight average molecular weight of 2000, the 1-hydroxycyclohexyl phenyl ketone solution and the chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is 0.2% recombinant human transforming growth factor-β1, 9% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone, 10% chitin whisker, and the remainder is solvent. The precursor solution is poured into the longitudinal large channel, and the lower bone repair scaffold material is obtained after cross-linking with ultraviolet light with a wavelength of 365nm for 8 minutes.

[0186] Step 4: Put a cylindrical silicone mold on the upper end of the lower bone repair scaffold material, 3 mm higher, mix baicalin solution, polyethylene glycol diacrylate solution with a weight average molecular weight of 4000, 1-hydroxycyclohexyl phenyl ketone solution and chitin whisker liquid crystal to obtain a liquid crystal precursor solution; wherein the content of each substance is calculated by mass percentage as follows: 0.05% baicalin, 9% polyethylene glycol diacrylate, 0.01% 1-hydroxycyclohexyl phenyl ketone, 8% chitin whisker, and the remainder is solvent. Inject the liquid crystal precursor solution into the upper mold and crosslink it with ultraviolet light at a wavelength of 365nm for 10 minutes. After complete crosslinking, demoulding is performed to obtain a bionic bone / cartilage double-layer composite scaffold material.

[0187] Pure polyethylene glycol diacrylate hydrogel was selected as a control group, and a precursor solution containing 9% polyethylene glycol diacrylate with a weight average molecular weight of 4000 and 0.01% 1-hydroxycyclohexyl phenyl ketone was prepared according to the mass fraction, injected into the upper mold for photocrosslinking for 10 minutes, and demolded after complete crosslinking to obtain the upper cartilage repair hydrogel material. At the same time, a polyethylene glycol diacrylate solution with a weight average molecular weight of 4000, a 1-hydroxycyclohexyl phenyl ketone solution and a chitin whisker liquid crystal were mixed to obtain a liquid crystal precursor solution, wherein the content of each substance was 9% polyethylene glycol diacrylate with a weight average molecular weight of 4000, 0.01% 1-hydroxycyclohexyl phenyl ketone, 8% chitin whiskers, and the remainder was solvent. The liquid crystal precursor solution was injected into the upper mold and crosslinked with ultraviolet light with a wavelength of 365nm for 10 minutes, and demolded after complete crosslinking to obtain the upper cartilage repair hydrogel material without encapsulating cartilage drugs.

[0188] The three groups of hydrogel materials were prepared into cylinders with a diameter of 10 mm and a height of 3 mm, and mouse mesenchymal stem cells were cultured (same as in Example 8). Fig.12 As shown, by performing Alcian blue staining on the mesenchymal stem cells on the upper hydrogel, we found that the introduction of chitin whisker liquid crystals can enhance the expression of the blue positive area. At the same time, the further introduction of baicalin promoted the increase of the positive area. The above results indicate that chitin whisker liquid crystals and baicalin have a certain synergistic effect in promoting the chondrogenic differentiation of stem cells.

[0189] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A bionic bone / cartilage double-layer composite scaffold material, characterized in that: It consists of an upper cartilage repair hydrogel layer and a lower bone repair scaffold layer; the upper cartilage repair hydrogel layer is a polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel containing a photoinitiator and a cartilage-promoting active drug; the lower bone repair scaffold layer includes a matrix scaffold and a liquid crystal channel structure, and the matrix scaffold is a polymer scaffold with transverse large channels and longitudinal large channels modified by polydopamine; A liquid crystal channel structure is constructed using a matrix scaffold as a template, wherein the lateral macrochannel has a chitosan-chitin whisker liquid crystal composite hydrogel micron radial channel with a diameter gradient change, and the longitudinal macrochannel contains a polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel encapsulating osteoangiogenic active drugs.

2. The bionic bone / cartilage double-layer composite scaffold material according to claim 1, characterized in that: In the upper cartilage repair hydrogel layer: The components in the polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel are as follows by mass percentage: 0.002% to 0.01% of photoinitiator, 0.005% to 0.1% of cartilage-promoting active drug, 4% to 10% of chitin whisker liquid crystal, and 1% to 10% of polyethylene glycol diacrylate; In the lower bone repair scaffold layer: The chitosan-chitin whisker liquid crystal composite hydrogel contains a crosslinking agent, chitosan and chitosan whisker liquid crystal; the components thereof are as follows by mass percentage: chitosan 0.5% to 5.0%, crosslinking agent 0.05% to 0.6% and chitosan whisker liquid crystal 5% to 12%; The polyethylene glycol diacrylate-chitin whisker liquid crystal composite hydrogel encapsulating osteogenic angiogenic active drugs contains osteogenic angiogenic active drugs, chitin whiskers and polyethylene glycol diacrylate; the components thereof are as follows by mass percentage: 0.001-0.05% of photoinitiator, 5%-15% of chitin whisker liquid crystal, 8%-15% of polyethylene glycol diacrylate, and 0.01%-1% of osteogenic angiogenic active drugs.

3. The bionic bone / cartilage double-layer composite scaffold material according to claim 2, characterized in that: In the upper cartilage repair hydrogel layer: The photoinitiator is at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate and 1-hydroxycyclohexyl phenyl ketone; The cartilage-promoting active drug is at least one of insulin-like growth factor, baicalin, bone morphogenetic protein, human parathyroid hormone-related protein and transforming growth factor; The weight average molecular weight of the polyethylene glycol diacrylate is 200-10000.

4. The bionic bone / cartilage double-layer composite scaffold material according to claim 2, characterized in that: In the lower bone repair scaffold layer: The polymer is at least one of poly(lactic acid), polycaprolactone and polyetheretherketone; The polymer stent is obtained by 3D printing; The steps of modification by polydopamine are as follows: placing the polymer scaffold in a dopamine reaction solution to react and obtain a matrix scaffold; The cross-linking agent is at least one of genipin, glutaraldehyde and epichlorohydrin; The weight average molecular weight of the polyethylene glycol diacrylate is 200 to 10000; The osteogenic and angiogenic active drug is at least one of bone morphogenetic protein, hypoxia inducible factor, vascular endothelial growth factor, transforming growth factor and deferoxamine; The photoinitiator is at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate and 1-hydroxycyclohexyl phenyl ketone.

5. The bionic bone / cartilage double-layer composite scaffold material according to claim 4, characterized in that: The weight average molecular weight of the L-polylactic acid is 50,000 to 350,000; The weight average molecular weight of the polycaprolactone is 50,000 to 200,000; The weight average molecular weight of the polyetheretherketone is 20,000 to 80,000; The concentration of the dopamine reaction solution is 0.5-5 g / L; The reaction conditions are 10-40° C. and 1-48 hours.

6. The bionic bone / cartilage double-layer composite scaffold material according to claim 2, characterized in that: In the lower bone repair scaffold layer: The large transverse channels are 1 to 4 layers, and the number of channels in each layer is 3 to 9; The outer diameter and inner diameter of the transverse macrochannel are 1-4 mm and 0.2-1.2 mm respectively; The diameter of the longitudinal macrochannel is 0.05 to 5 mm; The size of the micron radial channel is 1-100 μm.

7. The method for preparing the bionic bone / cartilage double-layer composite scaffold material according to any one of claims 1 to 6, characterized in that The steps include: (1) constructing a polymer scaffold using fused deposition 3D printing technology, immersing the polymer scaffold in a dopamine reaction solution for reaction, and obtaining a matrix scaffold after vacuum drying; (2) preparing a composite liquid crystal precursor solution of chitosan, a crosslinking agent and chitosan whiskers, and injecting the precursor solution into the transverse large channel of the base support obtained in step (1) for pre-crosslinking; (3) inserting a copper rod connected to a liquid nitrogen pool into the longitudinal large channel of the matrix support, radially freezing and freeze-drying, to obtain a support with micron radial channels; (4) preparing a precursor solution of osteogenic and angiogenic active drugs, polyethylene glycol diacrylate, a photoinitiator and chitin whisker liquid crystals, and injecting the precursor solution into the longitudinal macrochannel for photo-crosslinking to obtain a lower bone repair scaffold material; (5) A cylindrical silicone mold is placed on the upper end of the lower bone repair scaffold material, and a precursor solution prepared by cartilage-promoting active drugs, polyethylene glycol diacrylate, photoinitiator and chitin whisker liquid crystal is dripped into the mold for photocrosslinking. The mold is removed to obtain a bionic bone / cartilage double-layer composite scaffold material.

8. The preparation method according to claim 7, characterized in that: In step (1): When the polymer is L-polylactic acid, the 3D printing conditions are: the nozzle extrusion temperature is 150-250° C., and the printing speed is 25-60 mm / min. When the polymer is polycaprolactone, the 3D printing conditions are: the nozzle extrusion temperature is 60-80°C, and the printing rate is 20-40 mm / min; When the polymer is polyetheretherketone, the 3D printing conditions are: the nozzle extrusion temperature is 340-380°C, and the printing rate is 30-50 mm / min; In step (2): When the cross-linking agent is genipin, the pre-cross-linking time is 2 to 72 hours; When the cross-linking agent is glutaraldehyde, the pre-cross-linking time is 0.2 to 24 hours; When the cross-linking agent is epichlorohydrin, the pre-cross-linking time is 0.1 to 48 hours; The diameter of the copper rod described in step (3) is 0.1 to 5 mm; The radial freezing time in step (3) is 0.2 to 6 hours; The freeze drying process in step (3) is carried out at a temperature of -40 to -10°C and for a period of 4 to 24 hours; The time of the photocrosslinking in step (4) is 1 to 25 minutes; The cylindrical silicone mold described in step (5) is 0.5 to 5 mm higher than the underlying bone repair scaffold material; The time of the photocrosslinking in step (5) is 1 to 25 minutes.

9. Use of the bionic bone / cartilage double-layer composite scaffold material according to any one of claims 1 to 6 in the preparation of biomedical products.

10. The use according to claim 9, characterized in that: The biological application product is a bionic bone / cartilage repair scaffold.

Citation Information

Patent Citations

  • Double-layer bone-cartilage repair bracket and preparation method thereof

    CN110404108A

  • Photo-crosslinking chitin whisker composite liquid crystal gel material as well as preparation method and application thereof

    CN115197450A

  • Osteochondral integrated scaffold with directional pore structure and preparation method of osteochondral integrated scaffold

    CN116763995A

  • Bionic tissue stent, preparation method therefor and application thereof

    US20230293306A1